2004
DOI: 10.1186/1471-2431-4-13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of antinuclear antibody tests in children

Abstract: Background: Antinuclear antibody (ANA) tests are frequently used to screen children for chronic inflammatory diseases such as systemic lupus erythematosus (SLE). However, the diagnostic utility of this test is limited because of the large number of healthy children who have low-titer positive tests. We sought to determine the clinical utility of ANA tests in screening children for rheumatic disease and to determine whether there are specific signs or symptoms that enhance the clinical utility of ANA tests in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 17 publications
4
58
0
5
Order By: Relevance
“…In our study 65% of patients were with RA while 35% of patients werewith SLE, our RA percent similar to Julius et al [9]. In this study all patients with+ANA were with SLE while in others ANA have been detected in less than 10% to greater than 70% of patients with RA [10,11], they found that 7.5% of RA patients were+ANA and RF -ve. The peak age incidence in the recent study was differ from that others, in the recent were (20-24) of SLE and (30-34) of RA, while the west last studies found that the peak age incidence of SLE (15-25) and (25-35) of RA.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In our study 65% of patients were with RA while 35% of patients werewith SLE, our RA percent similar to Julius et al [9]. In this study all patients with+ANA were with SLE while in others ANA have been detected in less than 10% to greater than 70% of patients with RA [10,11], they found that 7.5% of RA patients were+ANA and RF -ve. The peak age incidence in the recent study was differ from that others, in the recent were (20-24) of SLE and (30-34) of RA, while the west last studies found that the peak age incidence of SLE (15-25) and (25-35) of RA.…”
Section: Discussionsupporting
confidence: 75%
“…This hypothesis is supported by the fact that environmental factors that associated with flares of lupus increase oxidative stress and subsequent apoptosis. Such factors include exposure to sun light and artificial UV light, pregnancy and infection 3 or may be due to some genetic factors, so further analysis in families have a history of RA and SLE may be helpful in predicting the detection of immune response and precise genetic susceptibility to RA and SILE, it will also be useful to include other gene markers like oil anti trypsine, which are thought to be associated with severe seropositive RA and SLE [13] from (Table 3 and 4) we can conclude that the incidence of SLE in female only in the following groups (10)(11)(12)(13)(14), (15-19) and (35-39). And no female or male patients with SLE in the following groups (40-44), and (50-54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'nın 20 94 KÜ tanılı çocukta yaptığı çalışmada sadece 2 hastada ANA titresi 1/160 üzerinde saptanmış olup, <1/180 ANA titresinin sistemik lupus açısından %100 oranında negatif prediktif değere sahip olduğu McGhee ve ark. 21 tarafından ileri sürülmüştür. Başka bir çalışmada ise 94 hastanın 2'sinde ANA pozitifliği saptanmış olup, hastaların birinde jüvenil romatoid artrit, birinde artralji saptanmıştır 6 .…”
Section: Discussionunclassified
“…All these methods are subject to false-positive results, mainly when the evaluated patient is in the age range over 60. [28][29][30][31][32] Substrates used for ANA detection by means of indirect immunofluorescence -FANA -can be from rat liver cells or human larynx tumor cells (Hep-2 cells). Hep-2 cells are better due to their large nucleus and to the easy exposure of their components.…”
Section: Identification Methodsmentioning
confidence: 99%